387 LAPAROSCOPIC REDO HELLER'S MYOTOMY FOR ACHALASIA FOLLOWING WORSENING OF SYMPTOMS DUE TO AN INADEQUATE MYOTOMY AND INAPPROPRIATELY CHOSEN ANTIREFLUX PROCEDURE. (14th September 2020) - Parshad, R; Verma, E; Sharma, R; Makharia, G
Abstract: : This patient underwent Laparoscopic heller's cardiomyotomy and Nissen fundoplication for Achalasia cardia at another institute. Following surgery his dysphagia worsened. Dysphagia persisted despite balloon dilatation. Patient was evaluated at our institute with Barium swallow and CECT thorax which showed dilated oesophagus with tight wrap. Patient was planned for laparoscopic re exploration. At surgery he had a Nissen wrap and inadequate extension of myotomy across the GE junction. Methods: The video describes the procedure of laparoscopic dismantling of the wrap with extension of Heller myotomy and a Toupet Fundoplication. Results: Patient had an uneventful recovery and had significant improvement in dysphagia at a follow up of 7 months. Conclusion: Nissen Fundoplication is not a good choice of antireflux procedure in achalasia cardia patients following Heller Myotomy and can contribute to dysphagia in the post operative period. Extension of myotomy across the GE junction is critical to the success of Heller myotomy. Re-do surgery is difficult but can be be accomplished through approach in experienced hands. Video: https://drive.google.com/file/d/1dhs-PlUm-ahDGF63VxxM0htB0dRiAGYJ/view?usp=sharing